Janeway's immunobiology - Murphy, Kenneth (Kenneth M.) (Garland Science, 2012)
This is a textbook that introduces the immune system in all its aspects to undergraduates, and also provides a treatment of the subject that is comprehensive enough to be useful to graduate students interested in research, and to medical students focused on clinical applications. The Eighth Edition has been thoroughly revised and updated.